Short Communication: Perception of synthetic biology application for biodiversity conservation among life science students in Institut Teknologi Bandung, Indonesia - RAHMAT AZHARI KEMAL (Smujo International, 2018)
Kemal RA. 2018. Short Communication: Perception of synthetic biology application for biodiversity conservation among life science students in Institut Teknologi Bandung, Indonesia. Nusantara Bioscience 10: 35-39. The emerging science of synthetic biology uses advanced engineering and biological science to re-design living organisms to carry out a specific function. Its application to biodiversity conservation seems promising yet barely addressed. Public perception of any emerging sciences and technologies should be studied. Therefore, this pilot study sought insight into the public perception of synthetic biology application to biodiversity conservation. As a pilot study, a web-based survey was designed for life science students in Institut Teknologi Bandung, Indonesia. Obtained responses were exported into Microsoft Excel and analyzed using SPSS 16.0. Results showed that respondents had a high agreement (>75%) on biodiversity problems, but the attitude toward risk in tackling problems is more cautious yet still open to new conservation technology. The respondents' overall perception of synthetic biology application for biodiversity conservation was positive (70% agreed/strongly agreed). The respondents perceived the application as risky but at the same time beneficial. There was a significant correlation between support for new technology development for biodiversity conservation with belief in promises that synthetic biology application's benefit (0.549, p<0.001). The respondents were still optimistic that the application would not decrease people's interest in biodiversity conservation. Results from this pilot study can serve as starting point for discussions and assessments of synthetic biology application in biodiversity conservation.